Optimalisasi Batang Pisang Menjadi Produk Olahan â€œDâ€™Bogzâ€ dengan Pemasaran Modern di Desa Prapaglor Kabupaten Purworejo - Rinawati, Anita; Tauryza, Fannies; Nisa, Laili Ainun; Wulandari, Sri; Asih, Niken Martselina (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to increase community productivity through the utilization of banana stems into D'bogz processed products with modern marketing in Prapaglor Village, Purworejo Regency. The partners of this activity were the PKK group of Prapaglor village consisting of 15 housewives who have potential in the field of product processing and want to become entrepreneurs. The method of implementing this service used counseling and training. The results of this service activity were that partners had the knowledge and skills to process banana stems into D'bogz products that have a selling value. In addition, partners also had skills in modern packaging and marketing so that the output targets were achieved in the form of Village SDGs targets in the context of village employment and economic growth, environmentally conscious village consumption and production towards healthy and prosperous villages within the framework of partnerships for villageÂ development.